Predictive factors of thrombosis during autologous stem cell transplantation in multiple myeloma: Experience from EHU Oran (Algeria) - Mohammed Amine BEKADJA; Brahim BENZINEB; Mansour BELKACEM; Hafida OUDJERIOUAT; Badra ENTASOLTAN; Soufi OSMANI; Kamila AMANI; Samira BOUCHAMA; Leila CHAREF; Mohamed BRAHIMI; Abdessamad ARABI; Rachir Amar BOUHASS; et al. (Journal de la Faculté de Médecine d'Oran)
Introduction-The objectives of our work are to measure the incidence of thrombosis and identify predictive factors during the procedure of autologous hematopoietic stem cells, during real life, in the University Hospital of Oran (Algeria). Methods-This is a retrospective study covering a period from 2009 to 2019. The diagnosis of thrombosis is made on the basis of clinical signs and symptoms of thrombosis and confirmed by a Doppler ultrasound of the site of location concerned or an angio-scanner, in the case of suspicion of arterial embolism, as well as D-Dimer elevation. The study focused on the overall incidence of thrombosis and the identification of predictive factors during the autograft procedure. Thepredictive factors studied are: age, co-morbidities, use of IMiDs, use of Granocyte colony stimualing factor in mobilization, the central venous catheter insertion site, cytapheresis count, CD34+ perfused, and finally deep venous thrombosis prophylaxis by a low molecular weight heparin .The statistical analysis focused on a univariate study, followed by a multivariate analysis using binary logistic regression. Results-Among 411 patients with MM underwent autologous transplantation of which 249 were male with a sex ratio of 1,53. The overall incidence of thrombosis was estimated at 18,49% (76 patients). The associative factors found in univariate analysis in our study are the use of IMiDs (p = 0,0006), the femoral KTC insertion site (p = 0,021) and its duration (p = 0,018), the level of G-CSG≥ 15μg/kg (0,014) during HSC mobilization and aplastic phase, the number of perfused CD34 +> 5x106/kg (p = 0,035) and prophylaxis with low molecular weight heparin (LMWH)(p = 0,029).In multivariate analysis, only the absence of LMWH prophylaxis was an independent predictor of thrombosis (p=0.001). Conclusion-Despite the similarity of the overall incidence of thrombosis with the literature, its prophylaxis with LMWHs was the only independent factor of its risk in Algeria, which would have restricted it in daily practice of autografts in multiple myeloma.